2010
DOI: 10.1007/s10482-010-9530-5
|View full text |Cite
|
Sign up to set email alerts
|

Standard YPD, even supplemented with extra nutrients, does not always compensate growth defects of Saccharomyces cerevisiae auxotrophic strains

Abstract: Conventional complex media are routinely used to grow auxotrophic strains under the assumption that they can compensate the latter's nutritional deficiencies. We here demonstrate that this is not always true. This study compares the growth parameters of Saccharomyces cerevisiae (S288C) and its derived auxotrophic strains FY1679-14C and BY4741 in synthetic minimal medium (SD), standard YPD medium from two of the most commonly used suppliers, or modified YPD medium. Maximum specific growth rates of auxotrophic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
1
25
1
1
Order By: Relevance
“…S288C-derived BY strains are auxotrophic for several amino acids and uracil; thus, auxotrophic supplements must be added, appropriate concentrations of which have been determined by considering the composition of the final biomass and the type of energy metabolism (Pronk [2002]). Auxotrophic supplementation is also necessary when using a complex medium, such as Yeast extract Peptone Dextrose (YPD) or grape must (Corbacho et al [2011]; Hanscho et al [2012]; Harsch et al [2010]). The optimal concentration of these supplements is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…S288C-derived BY strains are auxotrophic for several amino acids and uracil; thus, auxotrophic supplements must be added, appropriate concentrations of which have been determined by considering the composition of the final biomass and the type of energy metabolism (Pronk [2002]). Auxotrophic supplementation is also necessary when using a complex medium, such as Yeast extract Peptone Dextrose (YPD) or grape must (Corbacho et al [2011]; Hanscho et al [2012]; Harsch et al [2010]). The optimal concentration of these supplements is still under debate.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was expected because there had been many reports regarding the growth defect of auxotrophic strains. Even standard YPD could not compensate for the growth defects of S. cerevisiae auxotrophic strains (34,35). Nevertheless, the ATCC 4124 auxotroph still performed significantly better than three laboratory strains.…”
Section: Discussionmentioning
confidence: 93%
“…However, in our case we consider it more likely that the systematic discrepancy between fitness values is caused by a change in medium composition, which in turn has affected the relative reductive effect of each of the metals. YPD is a rich, undefined medium, and subtle changes in such media can have crucial consequences (Joho et al 1988;O'Keefe et al 2006;Corbacho et al 2011). In a pilot assay performed prior to this study, clone fitness correlated strongly with population fitness (data not shown).…”
Section: Appendix A2: Relative Fitness Of Evolved Clonesmentioning
confidence: 84%
“…First, the main problem that I came across was that fitness assays were sometimes irreproducible, particularly between batches of media. This problem is not specific to yeast, and might have been found with any organism cultured in undefined nutrient media (O'Keefe et al 2006;Corbacho et al 2011). It is possible that the consequences of variation in medium composition were particularly pronounced in my experimental set-up because metals have steep reaction norms (Joho et al 1988;Gadd 1993), such that small changes in effective concentration have far-reaching consequences for fitness.…”
Section: Strengths and Weaknesses Of The Model Systemmentioning
confidence: 95%
See 1 more Smart Citation